2022
DOI: 10.1007/s11904-021-00587-6
|View full text |Cite
|
Sign up to set email alerts
|

PEPFAR’s Role in Protecting and Leveraging HIV Services in the COVID-19 Response in Africa

Abstract: Purpose of Review We describe the impact of COVID-19 on PEPFAR programs in Africa and how PEPFAR adapted and leveraged its interventions to the changing landscape of the COVID-19 pandemic. Recent Findings To mitigate the potential impact of COVID-19 on the HIV response and protect the gains, continuity of treatment was the guiding principle regarding the provision of services in PEPFAR-supported countries. As the COVID-19 pandemic matured, PEPFAR’s approach evolved from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Partial Integration or Stand-alone services: TB and HIV/AIDS service delivery points are located in the same health facility; some HIV/AIDS services are provided in TB clinics, and some TB services are provided in HIV/AIDS clinics [49,50].…”
Section: Perceived Quality Of Integrated Tb/hiv Services By Character...mentioning
confidence: 99%
See 1 more Smart Citation
“…Partial Integration or Stand-alone services: TB and HIV/AIDS service delivery points are located in the same health facility; some HIV/AIDS services are provided in TB clinics, and some TB services are provided in HIV/AIDS clinics [49,50].…”
Section: Perceived Quality Of Integrated Tb/hiv Services By Character...mentioning
confidence: 99%
“…There are some challenges that impact negatively from partial integration model of TB and HIV integration, that have been encountered elsewhere by other studies elsewhere demonstrated [48, 50,51]:…”
Section: Perceived Quality Of Integrated Tb/hiv Services By Character...mentioning
confidence: 99%
“…Similarly, younger children were allowed refills in some countries at three or even 6-month intervals. Overall, MMD uptake increased from 46 to 70% in PEPFAR-supported countries [ 26 ••]. For the first time, children were represented within that marked percentage increase.…”
Section: Review Of the Literature: Pediatric Dsd Programming In The C...mentioning
confidence: 99%
“…Although the African continent reported relatively low COVID-19 cases, compared to other regions in the world, the impact of the pandemic on health service delivery was still very significant. Access to health facility-based services was interrupted as a result of 1) health workers shortages due to illness, self-quarantine, or strikes, 2) health facilities repurposed for COVID-19 treatment, covering minimum services, or closed completely, and 3) clients' reluctance to attend to visits, due to fear of increased risk of COVID-19 exposure, or decreased availability of public transportation (6,9,10). A review by Gizachew A.…”
Section: Introductionmentioning
confidence: 99%
“…From December 2020 to August 2022, MistraL reinforced the health system response (table 1), contributing to aspects such as: 1) support to the COVID-19 response coordination at district and national level; 2) addition of resources to improce health facilities infrastructure and provision of medical equipment; 3) integration of COVID-19/TB/HIV testing and linkage model; 4) addition and training of health workers for provision of services; and 5) implementation of research activities, including SARS-CoV-2 RTT tests validation in nasopharyngeal and nasal samples, or use and validation a of computer-aided diagnostic software for COVID-19 (CAD4COVID). In recent years, there has been an increasing interest to understand whether and how integrated screening and testing services could provide access to prompt COVID-19 diagnosis and management, while maintaining diagnostic and linkage services for TB and HIV, in an epidemic context (30)(31)(32). Nonetheless, to date, there have been few studies demonstrating feasibility or wider impact of such services in sub-Saharan Africa (33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%